Kid power strikes back - Pfeffer, Susan Beth, 1948- (New York : Scholastic, 1984)
Kid Power hits a slump when school begins but the coming winter gives twelve-year-old Janie new ideas on how to revive business. Sequel to "Kid Power."
Keywords: Moneymaking projects -- Fiction; Business enterprises -- Fiction; Family life -- Fiction